Structural–Functional Features of the Thyrotropin Receptor: A Class A G-Protein-Coupled Receptor at Work - Kleinau, Gunnar; Worth, Catherine L.; Kreuchwig, Annika; Biebermann, Heike; Marcinkowski, Patrick; Scheerer, Patrick; Krause, Gerd (Frontiers in Endocrinology, 2017)
The thyroid-stimulating hormone receptor (TSHR) is a member of the glycoprotein hormone receptors (GPHRs), a sub-group of class A G-protein coupled receptors (GPCRs). TSHR and its endogenous ligand thyrotropin (TSH) are of essential importance for growth and function of the thyroid gland and proper function of the TSH/TSHR system is pivotal for production and release of thyroid hormones (TH). This receptor is also important with respect to pathophysiology, such as autoimmune (including ophthalmopathy) or non-autoimmune thyroid dysfunctions and cancer-development. Pharmacological interventions directly targeting the TSHR should provide benefits to disease treatment compared to currently available therapies of dysfunctions associated with the TSHR or the thyroid gland. Upon TSHR activation the molecular events conveying conformational changes from the extra- to the intracellular side of the cell across the membrane comprises reception, conversion and amplification of the signal. These steps are highly dependent on structural features of this receptor and its intermolecular interaction partners, e.g. TSH, antibodies, small molecules, G-proteins or arrestin. For better understanding of signal transduction, pathogenic mechanisms like autoantibody action and mutational modifications, or for developing new pharmacological strategies, it is essential to combine available structural data with functional information to generate homology models of the entire receptor. Although so far these insights are fragmental, in the past few decades essential contributions have been made to investigate in-depth the involved determinants, such as by structure determination via X-ray crystallography. This review summarizes available knowledge (as of December 2016) concerning the TSHR protein structure, associated functional aspects and based on these insights we suggest several receptor complex models. Moreover, distinct TSHR properties will be highlighted in comparison to other class A GPCRs to understand the molecular activation mechanisms of this receptor comprehensively. Finally, limitations of current knowledge and lack of information are discussed highlighting the need for intensified efforts towards TSHR structure elucidation.